Implementasi Data Mining dengan Algoritma Naïve Bayes untuk Klasifikasi Kelayakan Penerima Bantuan Zakat Fitrah - Salsabila, Nanda; Ramury, Feli (UNIB Press, 2024)
In life there are many commands of Allah SWT. that must be carried out, one of which is the order to pay zakat. The purpose of this study was to classify the feasibility of receiving zakat fitrah at the mosque. The type of research used is quantitative research with quantitative descriptive research types. The classification that has been carried out assists the aid manager in making decisions regarding the classification of determining the recipients of zakat fitrah assistance. In this study, the Naive Bayes algorithm was implemented and analyzed using a web-based developed application. The results of the research show that the classification of zakat fitrah recipients is correct or valid.